Extracorporial Knots in Laparoscopic Surgery: Which, When, and How - Salem Khattab, Omar (Journal of the Faculty of Medicine Baghdad, 2008)
Despite recent advances in both suture welding and knotless anchor technology, knot tying will remain a necessary skill which the surgeon must master when performing suture anchor in laparoscopic surgery. There are an endless number of combinations of knots (sliding versus static, simple versus complex, etc.) and suture types (monofilament versus braided) to accomplish this task. Surgeons are familiar with knotting but seem not to be aware of the possibilities and impact of the techniques of capsizing, flipping, and flyping knots. (1) Capsizing refers to changing or perverting a flat knot’s geometry under asymmetric stress. The simplest examples of this is the change of the overhand knot into a half-hitch by putting more tension on its one end than on the other (Fig. 1A). (2,3,4) Flipping the knot means to interchange the standing part and working end of the suture, thereby relocating the knot from one end of the suture to the other.(5) The half-hitch can be flipped easily between both ends of a suture (Fig. 1B). Flyping (that rhymes with “typing”) is an archaic Scottish word that was used to describe the peeling off of a very wet glove of the hand, thereby changes its configuration from a righthand glove to a left-hand one. (6,7,8). The Scottish physicist Peter GuthrieTait (1831- 1901) introduced flyping as a knotting term, in the late-19th century, to define this “turning outside in” deformation process of the geometry of knots. (9) An illustrative example of flyping is the change of a series of turns of the working end around the standing part, into the proper blood knot geometry by drawing the proximal turns over the distal ones (Fig. 1C).